Exploration Ethnomathematics in Traditional Games of Mancala in Africa and Congklak in Indonesia - Suharti, Rita; Bhatt, Krishna Prashad; Tolulope, Owolabi Yemi; Sambo, Yahya A (jurnal matematika, 2025)
Purpose of the study: Study this aiming for explore draft ethnomathematics in game traditional Mancala in Africa and congklak in Indonesia use understand relatedness between culture and mathematics in context game. Methodology: With use approach qualitative ethnography, research this collect data through observation participatory, interview in-depth, and documentation to Mancala players in Ghana and congklak in Sumatra, as well as educators at school basis. Research results show that second game this involving draft mathematics like pattern numbers, distribution strategy, operations count, and thinking logical and probable. Main Findings: Experienced players show natural mathematical thinking through efficient strategies. While Mancala remains popular in Ghana, congklak is declining in Indonesia. Observations indicate traditional games have strong potential in culture-based math education. Thus, preservation and innovation are needed to integrate them contextually into learning. Novelty/Originality of this study: The novelty of this research lies in the exploration of the concept of ethnomathematics in the games Mancala in Africa and congklak in Indonesia through a qualitative ethnographic approach, which has not been studied in depth.